Human papillomavirus detection by the hybrid capture assay in the male genital tract - Carestiato, Fernanda N.; Silva, Katia C.; Prudente, Pedro H.P.; Silva, Licinio E.; Botelho, Mariza; Oliveira, Ledy H.S.; Cavalcanti, Silvia M.B. (Brazilian Journal of Sexually Transmitted Diseases, 2005)
Introduction: the Human Papillomavirus infection is the most disseminated viral sexually transmitted disease worldwide. Most part of the cases ofmale HPV infections are subclinical, and this conditions permit the dissemination of this virus silently. Objectives:To study the genital infectionscaused by the HPV, determining the prevalence of HPV types in male patients, attended at Laboratório Sergio Franco of the State of Rio de Janeiro,in 2001 and 2002. Methods: 1063 samples of male patients had been submitted the examinations for detection of HPV for the Technique of HybridCapture. Using the kit Digene (USA) Hybrid Capture® II HPV Test. Results: Among all the samples analyzed, 281 (26,4%) were positive to HPV,and 782 (73,6%) were negative to HPV. In positive samples 108 were infected by high-risk group (Group B), 97 by low-risk group (Group A), and76 were infected with both groups. The medium age of the participants was 30 years. Conclusion: This result showed a high prevalence of HPV inmen when compared to the rates encountered in developed countries. Our study considered that HCAII is a reliable test to detect HPV in male sam-ples and this conduct contributes to prevent the dissemination of this virus to women, where the HPV exerts their potential of malignant transforma-tion most efficiently